IMPORTANCE OF NANOCARRIERS AND PROBIOTICS IN THE TREATMENT OF ULCERATIVE COLITIS - THAKUR, VANDANA; SINGH, BHUPENDRA; SHARMA, ANKITA; KUMARI, NISHA; KUMAR, INDER; VERMA, KRITIKA; KUMAR, ARVIND; RANA, SUSHMITA (International Journal of Applied Pharmaceutics, 2021)
Ulcerative colitis (UC) is an inflammatory chronic disease primarily affecting the colonic mucosa; the extent and severity of colon involvement are variable. Ulcerative colitis is identified by mucus diarrhea, tenesmus, bowel distension, and anemia. 5-aminosalicylic acid drugs, steroids, and immune suppressants are used for the therapy of ulcerative colitis. The mainchallenges in the management of thediseaseare drug-related side-effects and local targeting. To overcome these challengesprobiotics and micro and Nanoparticulate systemauspiciousapproaches to overcome drug-related adverse side effects and local targeting.Upon ingestion, the probiotics can result in beneficial health effects. Probiotics and micro and nanoparticulate approaches for suitable targeting and overcome the drug-associated side effect. Probiotics are mainly used as gut modulators but are also nowadays explored for their use in ulcerative colitis.The current therapeutic goals are to achieve clinical remission along with mucosal healing, avoidance of complications such as side effects of the drug and to improve the quality of life. The use of probiotics to increase the health of the intestine and used to block or manage intestinal disorders. They may prevent the induction of inflammatory reactions. Probiotics must be inspected for efficacy in the prevention and management of a wide spectrum of gastrointestinal diseases, like antibiotic-associated diarrhea.Micro and Nanoparticulate drug delivery system has been achieving huge importance for targeting of the drug to colon locally at a controlled and sustained rate.